2019
DOI: 10.3389/fmicb.2019.01597
|View full text |Cite
|
Sign up to set email alerts
|

Negative Plant-Soil Feedback Driven by Re-assemblage of the Rhizosphere Microbiome With the Growth of Panax notoginseng

Abstract: There is a concerted understanding of the accumulation of soil pathogens as the major driving factor of negative plant-soil feedback (NPSF). However, our knowledge of the connection between plant growth, pathogen build-up and soil microbiome assemblage is limited. In this study, significant negative feedback between the soil and sanqi ( Panax notoginseng ) was found, which were caused by the build-up of the soil-borne pathogens Fusarium oxysporum , F. s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
62
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(85 citation statements)
references
References 73 publications
(92 reference statements)
7
62
1
Order By: Relevance
“…Similar findings were reported in our previous study on the rhizosphere microbiome of R. glutinosa based on barcoded pyrosequencing (Wu et al, 2018b). Luo et al (2019) indicated that P. notoginseng planting resulted in negative plant-soil feedback due to a decline in the beneficial rhizobacteria including the genera Pseudomonas and Bacillus in the rhizosphere. Pseudomonas spp.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similar findings were reported in our previous study on the rhizosphere microbiome of R. glutinosa based on barcoded pyrosequencing (Wu et al, 2018b). Luo et al (2019) indicated that P. notoginseng planting resulted in negative plant-soil feedback due to a decline in the beneficial rhizobacteria including the genera Pseudomonas and Bacillus in the rhizosphere. Pseudomonas spp.…”
Section: Discussionsupporting
confidence: 90%
“…However, large-scale crop monoculture results in many problems including a loss of crop genetic diversity, an increase in disease incidence, a decline in crop quality and even the fragility of ecosystem functioning (Jacques and Jacques, 2012;Mariotte et al, 2018;. Consecutive monoculture problems, also known as replant problems or replant disease, are especially severe in the cultivation of medicinal herbs, such as Rehmannia glutinosa, Panax notoginseng, Pseudostellaria heterophylla, and Panax ginseng (Dong et al, 2018a;Luo et al, 2019;Wu et al, 2019;Zhang et al, 2019). It was reported that approximately 70% of medicinal herbs using tuberous roots were attacked by replant disease (Wu et al, 2016c).…”
Section: Introductionmentioning
confidence: 99%
“…Inoculation of probiotic consortia may indirectly promote the growth of other beneficial bacteria and fungi, thereby suppressing root-rot. We found after sequencing that the abundance of Trichoderma in treatments A, B, C, and D gave better results as compared with control BT group; Trichoderma has been reported to be a biocontrol fungus having a wide range of antagonistic properties, and it can effectively inhibit the growth of F. oxysporum and Fusarium solani (Luo et al, 2019;Sallam et al, 2019). There was a negative relationship between the probiotic consortia abundance and Fusarium abundance, and inoculated probiotic consortia constrained Fusarium pathogen density.…”
Section: Inoculation Of Probiotic Consortia May Indirectly Promote Thmentioning
confidence: 88%
“…Individual colonies were picked out after incubating at 25°C for 4-5 days, and inoculated on NA media (bacteria) or PDA (fungi) to obtain pure cultures. The fungi were identified by a morphological method and ITS amplification (Luo et al 2019). The bacteria were identified through 16S rRNA amplification (Luo et al 2019).…”
Section: Isolation and Identification Of Culturable Fungi And Bacterimentioning
confidence: 99%
“…Ginsenosides were also demonstrated to inhibit the growth of Trichoderma hamatum but stimulate the growth of root rot pathogens (Nicol et al 2003;Yang et al 2015Yang et al , 2018b. Previous studies have found that the growth of P. notoginseng, P. ginseng, and P. quinquefolium could reassemble the rhizosphere microbiota and inferred that root exudates might be a key driving factor (Li et al 2012;Luo et al 2019;Jiang et al 2019). However, little is known about the effects of root exudates and ginsenosides in root exudates on the soil microbiota.…”
Section: Introductionmentioning
confidence: 99%